Immunometric and functional measurement of endogenous vasoinhibin in human sera - Zamora, Magdalena; Harris, David; Davies, Nils; Ebnet, Johannes; Radermacher, Peter; Brucker, Cosima; Waller, Christiane; Robles, Juan Pablo; Bertsch, Thomas; Clapp, Carmen; Triebel, Jakob (Frontiers in Endocrinology, 2024)
Circulating levels of the antiangiogenic protein vasoinhibin, a fragment of prolactin, are of interest in vasoproliferative retinopathies, preeclampsia, and peripartum cardiomyopathy; however, it is difficult to determine the circulating levels of vasoinhibin due to the lack of quantitative assays. This study used human serum samples to assess the concentration and bioactivity of vasoinhibin using a novel enzyme-linked immunosorbent assay (ELISA) for human vasoinhibin, which employs an antivasoinhibin monoclonal antibody, a human umbilical vein endothelial cell (HUVEC) proliferation assay, and a chick chorioallantoic membrane (CAM) angiogenesis assay. Serum samples from 17 pregnant women without (one group) and with and without preeclampsia and pregnancy induced hypertension (another group) demonstrated endogenous vasoinhibin concentrations in the range of 5-340 ng/ml. Immunoactive vasoinhibin levels were significantly higher in preeclampsia serum compared to healthy pregnancy serum (mean 63.09 ± 22.15 SD vs. 19.67 ± 13.34 ng/ml, p = 0.0003), as was the bioactive vasoinhibin level as determined by the HUVEC proliferation assay (56.12 ± 19.83 vs. 13.38 ± 4.88 ng/ml, p < 0.0001). There was a correlation between the concentration of vasoinhibin measured by ELISA and the HUVEC proliferation assay (Pearson r = 0.95, p < 0.0001). Healthy serum demonstrated a proangiogenic effect in the CAM assay (p < 0.05, compared to control), while serum from preeclamptic patients demonstrated an antiangiogenic effect (p < 0.05 vs. control), as did recombinant human vasoinhibin and a synthetic circular retro-inverse vasoinhibin analogue (CRIVi45-51). The antiangiogenic effects in the CAM assay and the inhibition of HUVEC proliferation were abolished by addition of the ELISA anti-vasoinhibin monoclonal antibody, but not by mouse IgG. These results demonstrate the first quantitation of endogenous vasoinhibin in human sera and the elevation of it levels and antiangiogenic activity in sera from women with preeclampsia. The development and implementation of a quantitative assay for vasoinhibin overcomes a longstanding barrier and suggests the thorough clinical verification of vasoinhibin as a relevant biomarker.